2004
DOI: 10.1109/led.2004.838557
|View full text |Cite
|
Sign up to set email alerts
|

Impact Ionization in Thin Silicon Diodes

Abstract: We study the breakdown behavior of thin, abrupt silicon pin-diodes, using a low-power optical technique which can directly measure the avalanche multiplication factors even in the presence of large tunneling currents. Our measurements agree with a simple model for nonlocal avalanche generation, and we use this model to extend the breakdown predictions to a broad class of doped diodes similar to those found in the base-collector region of bipolar devices. Based on this analysis, we make quantitative estimates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…The two experimental studies were similar, but more advanced, than the original work reported in 1957 [1]. The data in [8] is for diode depletion region widths down to 100 nm, while [9] extends the measurements to diode depletion region widths as small as 30 nm. Both reported avalanche gains very similar to the results previously published [3].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The two experimental studies were similar, but more advanced, than the original work reported in 1957 [1]. The data in [8] is for diode depletion region widths down to 100 nm, while [9] extends the measurements to diode depletion region widths as small as 30 nm. Both reported avalanche gains very similar to the results previously published [3].…”
Section: Introductionsupporting
confidence: 60%
“…Recently, photo-induced avalanche multiplication studies to measure the avalanche multiplication factors, even in the presence of large tunneling currents, were performed [8,9]. The two experimental studies were similar, but more advanced, than the original work reported in 1957 [1].…”
Section: Introductionmentioning
confidence: 95%
“…But they are usually built with waveguide cavity structure, which have complex circuit tuning and is sophisticated and difficult in system integration. Subsequently, kinds of integrated oscillator based on avalanche diode are developed, which have relative high output power but poor phase noise and frequency stability due to the operation character of oscillation mode [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The effective ionization coefficients were examined at each temperature and the values showing significant nonlocal effects, where α and β fall below the envelope, were removed from the data set. A regression algorithm was then used to fit a line described by (6) to the envelope of the remaining data points, yielding values for A and B. This is shown in Fig.…”
Section: T E CM (8)mentioning
confidence: 99%
“…The ionization process has been studied extensively at room temperature in thick Si structures [1 and references therein], however it is generally accepted that the ionization coefficients presented in [2] are the most accurate because of the large range of devices studied. There has been more recent interest in thin structures [3][4][5][6] where the dead space, the distance that carriers must travel in order for the ionization coefficients to achieve equilibrium with the electric field, becomes a significant proportion of the device width.…”
Section: Introductionmentioning
confidence: 99%